Tenaga Kependidikan: Pengawas/Kepala Sekolah - Desy Eka Citra Dewi; Eem Merani Destiana; Kristanti Olivia; Retno Ambar Wati; Reindo Febrianto (Universitas Maritim AMNI Semarang, 2024)
This study aims to analyze the preparation patterns of school principals and education supervisors, and to identify issues faced in their professional development. Based on the literature analysis, it was found that the preparation of prospective school principals and supervisors requires a comprehensive approach, including formal education, professional training, and practical experience in school management. The selection process, which is often limited to administrative tests, needs to be improved with competency-based assessments to ensure that prospective school principals and supervisors have the skills that match the demands of their duties. Professional development that is carried out continuously and based on practical learning is very important to improve the quality of leadership in schools. However, the challenges faced, such as limited resources in remote areas, require adjustments to training programs that are appropriate to the local context. The quality of training programs must also include broader aspects of leadership, including interpersonal skills and change management. External factors, such as education policies and community support, also have a major influence on the success of principal and supervisor preparation programs. In addition, a clear and performance-based career system can increase the professional motivation of principals and supervisors, thereby encouraging a more productive and innovative work culture. This study concludes that to produce quality principals and supervisors, holistic policies and integration of various aspects are needed in their preparation and development process.